Power Dynamics and Social Stratification in Pesantren: A Sociological Perspective - Muhammad Syaifullah; Noorazmah Hidayati (Research and Innovation in Social Science Education Journal (RISSEJ), 2026)
This study examines the dynamics of power and social stratification within pesantren and madrasah through a critical sociological lens. The analysis incorporates Max Weber’s theory of authority, Antonio Gramsci’s concept of hegemony, and Pierre Bourdieu’s framework of habitus, capital, and symbolic violence. Findings reveal that the authority of the Kyai is legitimized through scholarly lineage and spiritual obedience, producing a stable hierarchical structure supported by cultural hegemony. Social stratification emerges through a combination of ascribed status (genealogy) and achieved status (religious competence and functional roles), including the strategic contributions of the Nyai, Senior Students, and Santri Ndalem. Modernization and labor-market demands have stimulated structural changes, generating new institutional stratification between traditional (salaf) and modern pesantren. The study concludes that pesantren represents a dynamic social arena where spiritual power, social hierarchy, and modern pressures interact, shaping institutional resilience and the social mobility of its alumni.